1979
DOI: 10.3102/00028312016003241
|View full text |Cite
|
Sign up to set email alerts
|

Application of Alternative Statistical Techniques to Examine the Hierarchical Ordering in Bloom’s Taxonomy

Abstract: Working from data originally collected by Kropp and Stoker (1966) on the validity of Bloom’s Taxonomy, the present paper attempts to demonstrate that a multiplicity of analytic methods leads to a clearer conception of causal relationships than any single method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

1984
1984
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 9 publications
1
7
0
Order By: Relevance
“…The second branch consisted of the synthesis and evaluation could be identified with the fluid intelligence. These results were confirmed in the study conducted by Miller, Snowman and O'Hara in 1979 [5].…”
Section: Introductionsupporting
confidence: 71%
See 1 more Smart Citation
“…The second branch consisted of the synthesis and evaluation could be identified with the fluid intelligence. These results were confirmed in the study conducted by Miller, Snowman and O'Hara in 1979 [5].…”
Section: Introductionsupporting
confidence: 71%
“…As it was described in the introductory part, researchers as Madaus, Woods and Nuttal [4] as well as Miller, Snowman and O'Hara [5] used approaches similar to SEM to test BT validity. Validity researches conducted in the last twenty years have proven usefulness and necessity of SEM for that type of research [14].…”
Section: Structural Equation Modelingmentioning
confidence: 99%
“…Stoker and Kropp [13] found general support for the cumulative hierarchical nature of the taxonomy, but with the relationship between levels being less emphasized as the hierarchy is ascended. In Madaus et al [15] and Miller et al [16] both found that the data was better modeled by a 'Y' like structure, the base of the Y being made up of (from the bottom up) Knowledge, Comprehension and Application. Then Analysis was on one arm of the Y and Synthesis and Evaluation (in that order) were on the other arm.…”
Section: Introductionmentioning
confidence: 99%
“…Over the years, a number of investigations have been carried out into the validity of the taxonomy, with several of these directed specifically at the cumulative hierarchy property [13], [14], [15], [16], [17]. Stoker and Kropp [13] found general support for the cumulative hierarchical nature of the taxonomy, but with the relationship between levels being less emphasized as the hierarchy is ascended.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, some have suggested that synthesis and evaluation are not hierarchical but rather represent the same level of difficulty, using two divergent types of cognitive processes (Miller, Snowman, & O'Hara, 1979). Finally, some have questioned the epistemology of Bloom's work, noting that it is based on behaviorally specified goals wherein students have to demonstrate these cognitive levels in an observable way (Pring, 1971).…”
Section: Criticisms and Limitations Of Bloom's Taxonomymentioning
confidence: 99%